Developing Countries and Blockchain Technology: Uganda’s Perspective - Ivan, Niyonzima; Ruth Wario; Emmanuel Ahishakiye (International Journal of Latest Research in Engineering and Technology, 2018)
Blockchain is receiving ever-growing attention from research and industry and is considered a breakthrough technology. This paper presents an overview of Blockchain Technology and its potential applications in developing countries especially Uganda. It was noted that these nations have the potential to progress, but do not have adequate access to present day technology, primarily due to lack of infrastructure and thus Blockchain Technology will fill the gaps. Fundamentally, these nations need transparency, security, and accountability in their processes, all of which are cornerstones of Blockchain technology. Finally, this paper reveals that due to the support from both government and non-governmental organizations, and the establishment of the Blockchain Association of Uganda, Uganda is ready for Blockchain Technology.